Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1097/jto.0b013e3181952478
|View full text |Cite
|
Sign up to set email alerts
|

Vorinostat (NSC# 701852) in Patients with Relapsed Non-small Cell Lung Cancer: A Wisconsin Oncology Network Phase II Study

Abstract: No objective antitumor activity was detected with single agent vorinostat in this setting; however, it yields TTP in relapsed NSCLC similar to that of other targeted agents. Further studies in NSCLC should focus on combining vorinostat with other antitumor agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(70 citation statements)
references
References 34 publications
0
70
0
Order By: Relevance
“…Vorinostat, inhibits class I and II HDACs, has been approved by the Food and Drug Administration for treatment of cutaneous T-cell lymphoma and is known to have an anti-tumor effect against lung cancer cells. This agent has demonstrated disease stabilization as monotherapy in patients with advanced NSCLC [28]. In addition, combining vorinostat and a standard chemotherapy regimen, consisting of carboplatin and paclitaxel, increased the response rates in a phase II clinical trial involving metastatic NSCLC.…”
Section: Discussionmentioning
confidence: 98%
“…Vorinostat, inhibits class I and II HDACs, has been approved by the Food and Drug Administration for treatment of cutaneous T-cell lymphoma and is known to have an anti-tumor effect against lung cancer cells. This agent has demonstrated disease stabilization as monotherapy in patients with advanced NSCLC [28]. In addition, combining vorinostat and a standard chemotherapy regimen, consisting of carboplatin and paclitaxel, increased the response rates in a phase II clinical trial involving metastatic NSCLC.…”
Section: Discussionmentioning
confidence: 98%
“…In NSCLC cells, vorinostat induces significant G0/G1 cell cycle arrest and the induction of p21 WAF1 expression [15]. In addition, a small subset of NSCLC patients who were enrolled in a phase I clinical trial exhibited encouraging clinical responses to vorinostat monotherapy [11,16,17]. Notwithstanding the promising efficacy observed in these studies, a randomized phase II trial comparing paclitaxel/carboplatin (PC) versus PC with vorinostat [18] revealed only a modest improvement in median progression-free survival (6.0 months vs. 4.1 months; P = 0.48) and overall survival (13.0 months vs. 9.7 months; P = 0.17) in the vorinostat arm.…”
Section: Introductionmentioning
confidence: 98%
“…The most common side effects were diarrhea, fatigue, nausea, dysguesia, and thrombocytopenia, but were generally mild. In lung cancer, a phase II trial of single agent vorinostat in 14 refractory patients with NSCLC demonstrated no objective responses, but disease was transiently stabilized in 8 patients [36]. Based on this, carboplatin and paclitaxel were combined with escalating doses of vorinostat was tested in patients with solid tumors, and partial responses were observed in 10 of 19 patients with advancedstage NSCLC, which is higher than expected with chemotherapy alone [37].…”
Section: Histone Deacetylasesmentioning
confidence: 96%